Internal active cooling of a crystalline silicon photovoltaic module: Development of a modeling framework - Singh J.; Aditya Sabbineni M.; Jaiswal R.P. (My University, 2025)
Renewable energy sources are experiencing a resurgence in popularity due to growing environmental concerns. Solar technologies are the best renewable energy alternatives for meeting ever-increasing energy demand. The photovoltaic (PV) modules installed in a solar power plant get heated up quickly, resulting in significant reduction in their operating efficiency. This paper presents a mathematical model and its validation for a novel 'internal' active cooling mechanism, proposed elsewhere, for lowering the temperature of a crystalline silicon PV module. Specifically, a 3D mathematical model using COMSOL Multiphysics® software was developed to predict a silicon solar cell's temperature for conventional external and proposed internal cooling methods. The developed model was validated with the experimental data borrowed from the patent application (no. 202211050095). When compared to external air convection at a flow rate of 2 m/s, the proposed internal cooling method reduced the temperature of a Si solar cell by at least 5 °C. Finally, an economic analysis revealed that internal cooling could result in a 9.6 % net gain in the output of a solar power plant, compared to the 4.6 % net gain offered by external air cooling. © 2023 International Solar Energy Society